Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The availability of dimensions of creative leadership among secondary school principals in Wadi Al-Dawasir and its relationship to institutional excellence from the teachers’ point of view Mrs. Mitab Fahad Matruk Al-Dossary 2. The Degree of Transcendental Leadership Practice Among School Principals in The Directorate of Education, Al-Qasr/ Karak district Mrs. Widad Salim Al-Lassasmeh 3. The reality of the educational role of the secondary school in the educational region of Hail in achieving the social goals of sustainable development from the point of view of its teachers Mrs. Nawadir Murbih Alzabanii , Dr. Najla’ Muhamad Alhadif 4. The level of parents’ awareness of the importance of kindergarten in Hafar Al-Batin Governorate Mrs. Rawan Ali Al-Harbi 5. Self-efficacy beliefs and their impact on the ambition of students of higher education institutions in the Sultanate of Oman from their point of view Mrs. Sabra Saif Ahmed Alharrasi , Prof. Mastura Badzis 6. Assessment and Diagnosis barriers for Students with Communication Disorders from the Prospective of Speech Specialists in Al-Madinah Al-Munawwarah Mrs. Shatha Sabir Toukhi , Dr. Ghadah Ghazi Alharbi 7. Personal Traits of Teachers and Their Relationship to Their Job Satisfaction in The Sultanate of Oman Mr. Hilal Shamis Hamad Al-Thohli , Mrs. Nasra Saleh Abdullah Al-Abri